Work-Family Conflict, Work Stress and Its Relationship with Performance in the Life of Female Honorary Teachers During the Covid-19 Pandemic: Konflik Pekerjaan-Keluarga, Stres Kerja dan Hubungannya dengan Kinerja dalam Kehidupan Guru Honorer Wanita Selama Pandemi Covid-19 - Wahyuma, Nukhi Khusna; Kusuma, Kumara Adji (Indonesian Journal of Innovation Studies, 2023)
This study aims to find out Work-Family Conflict, Job Stress and Its Relationship with Performance Experienced by Female Honorer Teachers During the Covid-19 Pandemic. This research is a qualitative research with a phenomenological approach with data collection methods, namely interviews, observations and documentation. The informants in this study were ten honorer teachers who had multiple roles. The sampling technique used in this research is purposive sampling. The results showed that there was work-family conflict, work stress and had a relationship with performance in the lives of female honorer teachers. The factor of housewives to work outside the home is due to economic factors, educational factors, factors to fill spare time and also the dream factor. Individual conflicts, fatigue factors and the lack of time sharing between the dual roles they have. So that it triggers the emergence of work-family conflict, work stress and also the performance relationship in his life.